Microbial profiles and antimicrobial resistance patterns in neonatal intensive care units: an analysis of the impact of the COVID-19 pandemic in Indonesia - Santi, Theresia; Robertus, Thomas; Dewanto, Naomi Esthernita Fauzia; Hidayat, Feronica Kusuma; Hidayat, Ferry; Sungono, Veli; Jo, Juandy (Indonesian Pediatric Society, 2026)
Background Neonatal sepsis requires prompt antimicrobial treatment. A lack of information on patterns of antibiotic resistance among the bacteria across hospitals hinders the treatment. The COVID-19 pandemic contributed to changes in neonatal infection patterns and antimicrobial resistance. Data describing these changes remain scarce in Indonesia. Objective To determine the spectrum of pathogens and their antibiotic resistance patterns among Indonesian neonates with sepsis, prior and during the COVID-19 pandemic. Methods This retrospective study was done to examine patterns of pathogens and antibiotic resistance in neonates admitted to the neonatal intensive care units (NICUs) at Siloam Hospital Kebon Jeruk and Lippo Cikarang for 6 years, i.e., January 2018 to December 2020 (“Prior/Early COVID-19 Pandemic” or first phase) and January 2021 to December 2023 (“Mid/Late COVID-19 Pandemic” or second phase). The inclusion criteria were newborns with suspected or proven sepsis who underwent microbiological specimen collection for the assessment of antimicrobial resistance. We compared patterns of isolated pathogens and their antibiotic resistance of neonates with sepsis in two private hospitals, prior and during the COVID-19 pandemic. Results There were more participants in the first phase than in the second phase (44 vs. 33, respectively), resulting in more pathogenic isolates in the former than the latter phase (43 vs. 23, respectively). There were more Gram-negative bacteria detected than Gram-positive bacteria, although a reduction of several Gram-negative bacterial species from the order of Enterobacterales (including Klebsiella pneumoniae and Escherichia coli) was detected in the second phase. The resistance of Enterobacterales to gentamicin and third-generation cephalosporins was substantially increased in the second phase. Conclusion Despite an overall decline in isolate numbers, the observed increase in antibiotic resistance among Enterobacterales in the second phase may reflect suboptimal stewardship and indiscriminate use of broad-spectrum antibiotics during the COVID-19 pandemic. This highlights the growing challenge of antimicrobial resistance in neonatal sepsis management in Indonesia.